A case report of secondary B-cell acute lymphoblastic leukemia treated with a combination of FLT3 inhibitor and decitabine - Hu, Mengci; Li, Wenzhe; Li, Pan; Tan, Jie; Wang, Ya (Frontiers in Oncology, 2024)
Secondary acute lymphoblastic leukemia (s-ALL) refers to acute lymphoblastic leukemia that occurs after a previous malignant tumor, including therapy-related acute lymphoblastic leukemia (t-ALL) and prior malignant tumor acute lymphoblastic leukemia (pm-ALL) patients who have received chemotherapy and/or radiotherapy for a previous tumor and patients who have not received chemotherapy and/or radiotherapy. We report a case of a 51-year-old female patient who developed acute lymphoblastic leukemia 14 years after being diagnosed with diffuse large B-cell lymphoma (DLBCL). The patient was unresponsive to conventional chemotherapy for acute lymphoblastic leukemia (ALL) and achieved remission with a combination of sorafenib and decitabine based on the molecular biology characteristics of her B-ALL.